Dampak Pengembangan Desa Wisata terhadap Pendapatan Asli Desa dan Masyarakat di Desa Kemiren, Kecamatan Glagah, Kabupaten Banyuwangi - Anindita, Ryan Adha; Supranoto, Supranoto; Boedijono, Boedijono (University of Jember, 2019)
Abstract This study was aimed to describe the impact of tourism village development on Real Fund of Village and Community in Kemiren village, Glagah sub-district, Banyuwangi regency. Tourism is one of the revenue boosters with a bright prospect and minimal risk. The existence of holding customary norms was the uniqueness in this village. Tourism management in Kemiren Village was carried out by Tourism Concious Community (Pokdarwis) in collaboration with the government. Therefore, in this study, the researchers discussed the impact of tourism village development on Real Fund Village and Community that provided tourism services namely homestay rentals, souvenir sellers, art activists, studio owners, and restaurant owners. This descriptive research employed a quantitative approach. The research was conducted in Kemiren village, Glagah sub-district, Banyuwangi regency from July to August 2018. The population of this research consisted of 94 people including the owners of homestay, restaurants or cafes, art shop, and studio, as well as art activists. The sample of this research consisted of 48 people selected by random sampling technique. The data used in research consisted of primary and secondary data obtained through document review, questionnaires, and interviews. Then, the data were analyzed by using proportion analysis. Gradually, the tourism village development in Kemiren village was carried out on several aspects such as tourist attractions, accessibility, human resource development, promotion and partnerships as well as government activities in the village. The impact of income received by the village government on tourism business result increased the Village Real Fund by 18 percent in 2017 and 17 percent in 2018. In addition, community income increased in 2016 by 13.88 percent. The highest increase in 2017 was 35.94 percent, and in 2018, it was 16.61 percent. This information can be said that the development activities could increase the Real Fund of Village and Community.